2021
DOI: 10.1155/2021/8897826
|View full text |Cite
|
Sign up to set email alerts
|

3D Numerical Simulation of Landslides for the Full High Waste Dump Using SPH Method

Abstract: Waste dump that is generally composed of a large number of loose geotechnical materials is prone to landslides under external loads. In this work, the smoothed particle hydrodynamics (SPH) method combined with the Mohr–Coulomb model is used to study the dynamic characteristics of the landslides that occurred in the waste dump during the failure process. A benchmark test is firstly conducted to verify the effectiveness of the SPH model. Then, taking the Nanfen full high waste dump with a vertical drop of 300 m … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Chen et al [13] solved the problem of accurately locating sliding surfaces with tensile cracks in multistage landslide stability analysis and presented a new search method for multistage sliding surfaces: the discontinuous dynamic strength reduction method (DDSRM). Cao et al [14] proposed a smoothed particle hydrodynamics (SPH) method combined with the Mohr-Coulomb model to study the dynamic characteristics of the landslides that occurred during the destruction of dumps. Huang et al [15] indicated that the occurrence of landslides can be attributed to increasing incision depth and potential landslide energy.…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al [13] solved the problem of accurately locating sliding surfaces with tensile cracks in multistage landslide stability analysis and presented a new search method for multistage sliding surfaces: the discontinuous dynamic strength reduction method (DDSRM). Cao et al [14] proposed a smoothed particle hydrodynamics (SPH) method combined with the Mohr-Coulomb model to study the dynamic characteristics of the landslides that occurred during the destruction of dumps. Huang et al [15] indicated that the occurrence of landslides can be attributed to increasing incision depth and potential landslide energy.…”
Section: Introductionmentioning
confidence: 99%